The Effects of Unemployment on Health, Hospitalizations, and Mortality - Evidence from Administrative Data - Matija Vodopivec; Suzana Laporsek; Janez Stare; Milan Vodopivec (Institute of Labor Economics (IZA), 2021)
Linking health to the employment history of the whole Slovenia's workforce, this paper employs three innovative features. First, it utilizes a novel "double proof" approach of addressing the reverse causality that tracks only healthy individuals, making sure that any unemployment spell that individual may undergo precedes the occurrence of a disease, and relies on mass-layoffs to provide an additional layer of exogeneity to unemployment. Second, it is one of the first papers using data on drug prescriptions to infer information about the health status of individuals and link it labor market outcomes. And third, it treats the health effects of unemployment as part of a dose-response relationship, with the share of time spent in unemployment (as opposed to other labor market states) reflecting the "unemployment dose". The paper finds that, in comparison to employed persons with permanent contracts, persons experiencing unemployment face increased hazard of all three studied groups of diseases - cardiovascular diseases, diabetes, and mental disorders - as well as of hospitalizations caused by these diseases, with the effects stretching over a 15-year horizon. Moreover, the results also show that unemployment significantly increases the probability of death due to cardiovascular diseases and mental disorders, as well as death of any cause.
Keywords: J64; I12; C23; 330; unemployment; health; hospitalization; mortality; cardiovascular diseases; diabetes; mental disorders; prescriptions; duration analysis